1988
DOI: 10.1007/bf00361656
|View full text |Cite
|
Sign up to set email alerts
|

The role of magnetic resonance imaging in the evaluation of Ewing sarcoma

Abstract: The experience with magnetic resonance imaging (MRI) in 27 patients with Ewing sarcoma is reported and compared with computed tomography (CT) and plain films. Plain radiography proved to be the best imaging method to asses probable histological diagnosis in all cases (n = 6). For the evaluation of chemotherapeutic response (n = 4), CT and MRI gave the same information about the variation in size of the tumor. In this small series, the high signal in T2 weighted images was not altered significantly by therapy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(15 citation statements)
references
References 16 publications
3
12
0
Order By: Relevance
“…There was one case of malignant giant cell tumour of humerus, which showed cortical permeation and an associated soft tissue mass as shown by Murphey et al 7 One case of Ewing's sarcoma was present in our study, which was confirmed on histopathology in which MRI gave better information on soft tissue involvement and extension within the bone marrow similar to study done by Frouge C et al 8 Two cases of sacrococcygeal chordoma were present in our study, which showed adjacent soft tissue involvement and bilateral sacroiliac joints involvement was seen in one case.…”
Section: Discussionsupporting
confidence: 88%
“…There was one case of malignant giant cell tumour of humerus, which showed cortical permeation and an associated soft tissue mass as shown by Murphey et al 7 One case of Ewing's sarcoma was present in our study, which was confirmed on histopathology in which MRI gave better information on soft tissue involvement and extension within the bone marrow similar to study done by Frouge C et al 8 Two cases of sacrococcygeal chordoma were present in our study, which showed adjacent soft tissue involvement and bilateral sacroiliac joints involvement was seen in one case.…”
Section: Discussionsupporting
confidence: 88%
“…33). MRI is the best diagnostic modality in evaluating the medulla of bone and the extent of the medullary involvement [145]. Biopsy then confirmed the diagnosis of Ewing's sarcoma.…”
Section: Periosteal Fibrosarcomamentioning
confidence: 97%
“…The most precise definition of the local extent of disease, including the intramedullary portion and the relation of the lesion to adjacent blood vessels and nerves, is provided by magnetic resonance imaging (MRI) (Fig. 2) [3,[7][8][9][10].…”
Section: Presentationmentioning
confidence: 99%